Gut microbiota as a target in the bone health of livestock and poultry: roles of short-chain fatty acids - Shu-Cheng Huang; Yan-Feng He; Pan Chen; Kai-Li Liu; Aftab Shaukat (BMC, 2023)
Abstract The regulation and maintenance of bone metabolic homeostasis are crucial for animal skeletal health. It has been established that structural alterations in the gut microbiota and ecological dysbiosis are closely associated with bone metabolic homeostasis. The gut microbiota and its metabolites, especially short-chain fatty acids (SCFAs), affect almost all organs, including the bone. In this process, SCFAs positively affect bone healing by acting directly on cells involved in bone repair after or by shaping appropriate anti-inflammatory and immunomodulatory responses. Additionally, SCFAs have the potential to maintain bone health in livestock and poultry because of their various biological functions in regulating bone metabolism, including immune function, calcium absorption, osteogenesis and osteolysis. This review primarily focuses on the role of SCFAs in the regulation of bone metabolism by gut microbiota and provides insight into studies related to bone health in livestock and poultry.